Food / Ethnographic Encounters - Coleman Leo (Bloomsbury, 2011)
This book presents fascinating essays about cooking, eating and sharing food by anthropologists working in many parts of the World, exploring what they learned by eating with others. Introduction, Food and Morality in Yemen, It All Started with the Bhajas, The Enchantments of Food in the Lower Amazon in Brazil, Live Poultry Markets and Avian Flu in Hong Kong, Revisiting Lao Food: Pain and Commensality, In Search of the Elusive Heirloom Tomato: Farms and Farmers' Markets and Fields and Fieldwork, Keeping Out of the Kitchen: Cooking and Power in a Moroccan Household, Do You Know How to Eat? Edible Expertise in Ho Chi Minh City, Learning to Exchange Words for Food in the Marquesas, Eating Vegetarian in Vietnam, The Food of Sorrow: Humanitarian Aid to Displaced People, Guide to Further Reading.